From the Memories to a Sensorial History of the School in the Province of Paraná - Juarez José Tuchinski dos Anjos (Universidade Federal do Rio Grande do Sul, 2019)
Based on the considerations of Silva and Vidal (2011), it was developed the hypothesis that it is possible to evidence some experiences of what the elementary school in Imperial Brazil delivered to children. This was done by means of a sensory history, based on the individual and collective contacts with school materiality evoked in memorialistic records, making explicit the meanings assigned to the school and the schooling received during that historical moment. This article aims to conduct an initial approach to this matter, identifying the sensory experiences that occurred in a school of city of Paranaguá, in the coast of the Province of Paraná along the 1870s, in the life of Nestor Vitor dos Santos, one of the students who attended it.